Development of a TaqMan-based multiplex real-time PCR for simultaneous detection of four feline diarrhea-associated viruses - Zou, Junwei; Yu, Ju; Mu, Yuanyuan; Xie, Xiangyu; Wang, Run; Wu, Haiqiang; Liu, Xuan; Xu, Fazhi; Wang, Juhua; Wang, Yong (Frontiers in Veterinary Science, 2022)
Since their recent discovery, novel feline enteroviruses including feline bocavirus-1 (FBoV-1), feline astrovirus (FeAstV), and feline kobuvirus (FeKoV) have been reported to be prevalent in China. These viruses are commonly co-infected with feline parvovirus (FPV) and cause viral diarrhea in cats. Viral co-infection is difficult to identify owing to identical clinical signs. To detect and identify these viruses, a quick and specific pathogen-testing approach is required. Here, we establish a qPCR detection technology based on multiple TaqMan probes for the simultaneous detection of FPV, FBoV-1, FeAstV, and FeKoV. Specific primers and TaqMan fluorescent probes were designed to ensure specificity. The results revealed that the detection limit of single qPCR was up to 10 copies, and the detection limit of multiplex qPCR was up to 100 copies, with correlation coefficients greater than 0.995 in all cases. Clinical sample detection showed that the total rate of coinfection among the viruses was 25.19% (34/135), and the quadruple infection rate was 1.48% (2/135). The multiplex qPCR approach described in this study can serve as a quick, sensitive, and specific diagnostic tool for FPV, FBoV-1, FeAstV, and FeKoV identification, and it may be utilized for routine surveillance of these emerging and reemerging feline enteroviruses.